Arbacia - GIANGUZZA, Paola; BONAVIRI, Chiara (Elsevier, 2013)
Sea urchins of the genus Arbacia are widely distributed throughout the world occurring in tropical, temperate and sub-Antartic zones. In the past, Arbacia has been the object of intensive investigations in cell biology and biochemistry of fertilization and early development. Renewed interest in the genus Arbacia arose mainly due to its ecological role and its unusual geographic distribution. All the six species of Arbacia are omnivorous with a strong tendency to carnivory. Recent manipulative and morpho-functional studies demonstrated that Arbacia species play an important role in the ecology of rocky reefs. They maintain barren areas by scraping either fleshy and encrusting algae and animals from the substrata, thanks to their large Aristotle’s lantern, indicative of a durophagic habit. The genus Arbacia is distributed in both high and low latitudes, and its phylogeny does not confirm the tendency of marine species to arise in the tropics and then spread into the temperate zone. Arbacia is a gonochoric genus with a very early maturity. Generally Arbacia species show a reproductive cycle typically annual or semi-annual. Some species of this genus (i.e. A. lixula) seem to be favored by the increase of temperature. These findings point out the potential role of Arbacia in a scenario in which the mean global temperature of sea surface and the frequencies of temperature anomalies are increasing and the necessity to amply the study on biology and ecology of this genus.